EFFECTS OF ALPHA-MANGOSTIN AND CITRONELLA OIL AGAINST ACNE CAUSING BACTERIA - TANNGOEN, PIANGPETCH; Lamlertthon, Supaporn; Tiyaboonchai, Waree (International Journal of Pharmacy and Pharmaceutical Sciences, 2019)
Objective: This study assessed the effects of alpha-mangostin (AM) and citronella oil (CO) working alone or in combination against Propionibacterium acnes (P. acnes) and Staphylococcus aureus (S. aureus). Methods: The screening for antibacterial activity of AM and CO against P. acnes and S. aureus was carried out using the disk diffusion method. The minimum inhibitory concentrations (MICs) and minimum bactericidal concentrations (MBCs) of these two substances were determined using the broth microdilution method. The fractional inhibitory concentration indices (FICI) of a combination of AM and CO were obtained by checkerboard dilution assay. Results: The results showed that alpha-mangostin and citronella oil do indeed fight against P. acnes and S. aureus. The MICs and MBCs of AM against P. acnes and S. aureus were the same at 6.25 and 50 µg/ml, respectively. Both the MIC and the MBC of CO against P. acnes were 27.81µg/ml. The MIC and the MBC of CO against S. aureus were 112.13 and 224.25 µg/ml, respectively. The FICI of a combination of AM and CO against P. acnes and S. aureus were 2.00, indicating indifferent interaction with no additional inhibitory effect. Conclusion: AM and CO are very effective against P. acnes and S. aureus, nevertheless their effect when used together was indifferent from using alone. Further research may find that either or both of these substances combined with yet a different natural agent could provide synergy againstP. acnes and S. aureus.